Disturbed Th17/Treg balance, cytokines, and miRNAs in peripheral blood of patients with Behcet's disease. Issue 4 (14th October 2018) - Ahmadi, Majid; Yousefi, Mehdi; Abbaspour‐Aghdam, Sanaz; Dolati, Sanam; Aghebati-Maleki, Leili; Eghbal‐Fard, Shadi; Khabbazi, Alireza; Rostamzadeh, Davood; Alipour, Shahriar; Shabani, Mahdi; Nouri, Mohammad; Babaloo, Zohreh
Abstract: Impaired inflammatory immune cells have been implicated in the pathogenesis of Behcet's disease (BD). In the current study, we aimed to evaluate the frequency of T helper (Th) 17 and regulatory T (Treg) cells, cytokine secretion, the expression of transcription factors related to Th17 and Treg cells, and microRNAs (miRNAs) targeting these transcription factors in BD patients. Blood samples from 47 BD patients and 58 healthy subjects were drawn, and the peripheral blood mononuclear cells (PBMCs) were separated and isolated. The frequency of Th17 and Treg cells was assessed using flow cytometry. Transcription factors related to these cells and miRNAs targeting these transcription factors were quantified using real‐time polymerase chain reaction. Finally, the levels of associated cytokines were measured using enzyme‐linked immunosorbent assay. A significant reduction in the percentage of Treg cell frequency and the levels of interleukin (IL)‐10 and forkhead box P3 messenger RNA (mRNA) expressions were observed. The proportion of Th17 cells was notably increased, which was accompanied by a increased levels of IL‐17, IL‐23, and retinoic acid‐related orphan receptor ɣ (RORɣt) mRNA expressions in BD patients. The level of Th17‐associated cytokines in the supernatant was found to be elevated in BD patients. T‐cell‐associated miRNA expression levels, miR‐25, miR‐106b, miR‐326, and miR‐93 were significantly upregulated, while miR‐146a and miR‐155 levels were lower in PBMCs of patients with BD when compared with the controls. The increase in the proportion of Th17 cells alongside the decrease in Treg cells are possibly the involving factors in the pathogenesis of BD. Therefore, the evaluation of immune cells and related miRNA profile may serve as both prognostic biomarker and therapeutic approach in treating patients with BD.